ANALISA KUALITAS AIR TAMBAK DESA KALANGAYAR KECAMATAN SEDATI KABUPATEN SIDOARJO - Widiyanti, Atik (Journal of Research and Technology, 2017)
The decline of water quality is known to have a lot going on. One of them is the pond in the village Kalanganyar Sedati District Subdistrict Sidoarjo. Therefore, this study aims to determine the water quality and the type of ectoparasites that often infect fish in the pond. Parameters measured include Total Suspended Solid (TSS), Salinity, Detergents, TPC, and ectoparasites. The analysis TSS, salinity, detergent, TPC, and ectoparasites were performed by using methods gravimetri, salinometer, spectrophotometry, TPC, and microscopic sequentially. Ectoparasites samples were taken from fish (Chanos chanos) and water quality samples were taken from the upstream and downstream of the pond. Results of water upstream analysis of the pond shows the TSS concentration of 80 mg/l; 61.80 ppt salinity; detergents 3.08 mg/l LAS, and TPC 220 cells/ml. While downstream of TSS concentration of 116 mg/l; 37.90 ppt salinity; detergents 1.29 mg/l LAS and TPC 1780 cells/ml. Group of ectoparasites found were Nematoda, Protozoa, crustacean, and trematodes.